Intercultural communication in a discussion about t-shirts on the online forum mystcommunity.com - Bastiko Pradhana (UPT P2M Politeknik Negeri Malang, 2014)
As people progress in life, they invariably come into contact with other people. One place where intercultural communication can occur is on the Internet, and in particular on online forums. One of these forums is MYSTcommunity.com, a discussion forum specifically created for fans of the computer game Myst to discuss developments in this series as well as anything related to it. This study shows that intercultural communication does not always result in failure. The identity of the female members perfectly represents how culture can be acted and not just referred to. By making use of their situational discourse system, in particular face systems and strategies, as well as their community of practice, they produced communication that spoke for themselves, their identity, and how they should be perceived. The female members are aware that what they do represents what they are, and so they made use of the cultural tools in their discourse system and communities of practice to show the best way to participate. As a result, they do not come off as being misunderstood; instead, they made themselves understandable; they created communication that bridged their perceptions with the others, making the communication successful.